Effects of physiological levels of daidzein on cell proliferation of tumoral and non-tumoral breast cells lines - Tsuboy, Marcela Stefanini Ferreira [UNESP]; Marcarini, Juliana Cristina [UNESP]; Souza, Alecsandra Oliveira de; Paula, Natalia Aparecida de; Luiz, Rodrigo Cabral; Dorta, Daniel Junqueira; Mantovani, Mário Sérgio; Ribeiro, Lucia Regina [UNESP] (My University, 2014)
Introduction: Soy isoflavones are associated with the lower breast cancer risk found in Asiatic populations. They can interfere in various stages of the carcinogenesis process, preventing the development of this pathology and, for this reason, its consumption became popular. Instead of the beneficial effects found in literature, most chemopreventive in vitro studies use non-physiological levels of daidzein (> 30 µM). In our study, the effects of maximal physiological levels of daidzein was investigated in two human breast cell lines: HB4a (non-tumoral) and MCF-7 (tumoral). Experiments to verify cytotoxicity, induction of cell death by apoptosis and, additionally, cell cycle arrest were performed. Materials and methods: Cytotoxic effect of daidzein (0.1 - 100 µM) was assessed using resazurinbased assay. Flow cytometry tests were performed to investigate apoptosis induction (annexin VFITC/PI) and cell cycle arrest (propidium iodide staining of DNA content) by daidzein at 10 and 25 µM. Changes in expression of apoptosis related genes after treatment of cells with daidzein (10 and 25 µM) were investigated using quantitative real time PCR. Results: Daidzein ranging from 0.1 to 100 µM (for 24 and 48h) were not cytotoxic to both cell lines. Concentrations of 10 and 25 µM did not induce apoptosis in these cells, instead of statistical significant changes in gene expression of some of the target genes (CASP-3, CASP-7, BAX, BCL-xL, COX-2). Both concentrations of daidzein arrested cell cycle in G0/G1 phase only in MCF- 7. Conclusion: Daidzein at maximal achievable physiologic serum levels selectively arrested cell cycle only in the tumoral MCF-7, and did not induce cell death by apoptosis, one of the major effects described in literature. We hope that our study helps in understanding the chemopreventive effects of low levels of soy isoflavones in breast carcinogenesis.